(untitled) (Bulletin of Environmental Science and Sustainable Management (e-ISSN 2716-5353), 2022)
Acrylamide pollution and contamination can come from a variety of sources and is an emerging toxic pollutant that need remediation. A molybdenum-reducing bacteria that had been previously isolated and demonstrated the ability to degrade amides was further studied of its critical parameters contributing to optimum growth on acrylamide. The Box-Behnken design was utilized in optimizing the three previously identified significant components (pH, incubation time and acrylamide concentration). ANOVA, the pertubation’s plot, and several other diagnostic plots were utilized in the analysis of the significant factors or parameters that contributed. The model was supported by the diagnostic plots including the half-normal, Cook’s distance, leverage vs runs, residual vs runs, Box-Cox, DFFITS, and DFBETAS. Conditions that were predicted to be optimal were found and analyzed in order to find the optimal growth given the factors that were used and to determine the optimal concentration, which was 1 g/L. The solutions for finding the optimal growth predicted a growth maximum of 12.055 Log CFU/mL (95 percent confidence interval (C.I.) from 11.550 to 12.593), and verification using experimental results resulted in a growth of 12.908 Log CFU/mL (12.744 to 13.072) with the results being close to the predicted values but was significantly higher than the predicted data. The second numerical optimization was for predicting the highest acrylamide concentration tolerable for growth and the solution shows a predicted a growth maximum of 12.055 Log CFU/mL (95 percent confidence interval from 11.550 to 12.593). This solution was experimentally verified resulting in a growth of 12.195 Log CFU/mL (95 percent confidence interval from 11.806 to 12.584) with the actual results being in accordance with the predicted values. The results of the RSM exercise showed that growth on acrylamide may be optimized more effectively with RSM than with OFAT, which indicates that RSM is more useful than OFAT in this regard.